Whole-body vibration administered during a 3-week in-hospital multidisciplinary body weight reduction program increases resting energy expenditure in obese adolescents, a randomized clinical trial - Tamini, Sofia; Tringali, Gabriella; De Micheli, Roberta; Bernardo-Filho, Mario; de Sá-Caputo, Danúbia da Cunha; Sartorio, Alessandro (Frontiers in Endocrinology, 2025)
BackgroundPediatric obesity is a growing global health concern, and interventions aimed at increasing resting energy expenditure (REE) have gained attention as complementary strategies to dietary restriction. Whole-body vibration (WBV), an innovative exercise mimetic, may offer metabolic and functional benefits, particularly in populations with limited exercise tolerance. This study was a randomized clinical trial aimed to evaluate the effects of incorporating WBV into a 3-week in-hospital multidisciplinary body weight reduction program (BWRP) in male adolescents with obesity.MethodsTwenty-three male adolescents with obesity (mean age: 15.7 ± 1.3 years; mean body mass index (BMI): 38.5 ± 5.6 kg/m2) hospitalized for a 3-week BWRP were randomly assigned to a control group receiving the standard BWRP (subgroup A, n = 12) or an experimental group receiving BWRP plus WBV sessions (subgroup B, n = 11). Anthropometric and clinical parameters, REE, and lower limb muscle power, evaluated using the stair-climbing test, were assessed before and after the intervention.ResultsBoth subgroups demonstrated significant reductions in body weight and BMI. REE showed a significant Time × Group interaction (p < 0.01), indicating differential responses between the two intervention groups. WBV training significantly increased REE in subgroup B, from 2470.1 ± 249.6 kcal/day at baseline to 2733.0 ± 310.8 kcal/day post-intervention (Δ = +262.9 kcal, p < 0.001). In contrast, subgroup A showed no significant change in REE, with values decreasing from 2204.0 ± 307.4 kcal/day to 2020.8 ± 442.5 kcal/day (Δ = ˗183.2 kcal, p = ns). REE change was supported by significant Time × Group interaction in a two-way repeated measures ANOVA (p = 0.002). Furthermore, a significant post-intervention correlation emerged between REE and anaerobic power only in subgroup B.ConclusionThe addition of WBV to a structured BWRP significantly increased REE in obese adolescents, beyond the effects of the BWRP alone. This finding supports the use of WBV as a promising adjunct strategy to conventional interventions in pediatric obesity.